MicroRNA-19b-3p promotes cell proliferation and osteogenic differentiation of BMSCs by interacting with lncRNA H19 - Gan Xiaoling; Liu Shuaibin; Liang Kailu (BMC, 2020)
Abstract Background To investigated the role of miR-19b-3p in regulating bone marrow mesenchymal stem cell (BMSC) proliferation and osteoblast differentiation. Methods The expression of miR-19b-3p and lncRNA H19 were measured in postmenopausal osteoporosis patients and BMP-22 induced BMSCs using qRT-PCR. MiR-19b-3p mimic or inhibitor was transfected into BMP-2 induced BMSCs. Cell proliferation was measured by BrdU method. Protein expression of RUNX2 and COL1A1 were measured by western blot. PcDNA3.1-lncRNA H19 with or without miR-19b-3p mimic was transfected into BMP-2 induced BMSCs. Results The expression of miR-19b-3p was significantly up-regulated in postmenopausal osteoporosis patients and BMP-2 induced BMSCs. MiR-19b-3p overexpression dramatically elevated, while miR-19b-3p inhibition decreased cell proliferation of BMSCs. Additionally, protein expression levels of RUNX2 and COL1A1, as well as ALP activity were significantly promoted by miR-19b-3p mimic transfection and inhibited by miR-19b-3p inhibitor transfection. LncRNA H19 was obviously down-regulated in postmenopausal osteoporosis patients. H19 overexpression significantly decreased cell proliferation and differentiation by down-regulating miR-19b-3p. Moreover, the expression of miR-19b-3p was inhibited, while H19 elvated in 17β-estradiol (E2) treated BMSCs in a dose-dependent manner. Conclusion These data were the first to reveal the critical role of H19/miR-19b-3p in postmenopausal osteoporosis, and provided a new therapeutic target for OP.